Adoption and potential of agri‐environmental schemes in Europe: Cross‐regional evidence from interviews with farmers - Bartosz Bartkowski; Michael Beckmann; Marek Bednář; Sofia Biffi; Cristina Domingo‐Marimon; Minučer Mesaroš; Charlotte Schüßler; Bořivoj Šarapatka; Sonja Tarčak; Tomáš Václavík; Guy Ziv; Felix Wittstock (People and Nature, 2023)
Abstract In Europe and elsewhere, agri‐environmental schemes (AES) are designed to reduce agriculture's impacts on the environment. Designing effective schemes requires an understanding of the reasons that drive farmers' decisions whether to adopt AES. Currently, most insights come from individual case studies or structured surveys based on predefined questions. There is a paucity of studies that do not rely on rigid preconceptions about relevant behavioural factors while also offering a geographically and socio‐culturally broad perspective that can address the cultural and institutional context‐specificity of behavioural studies. Also, most studies focus on the adoption decision, while implementation decisions and their consequences for the ecological effectiveness of AES remain understudied. In this article, we present the results from semi‐structured farmer interviews conducted in five agricultural landscapes across Europe. The results are used to uncover reasons for AES adoption as well as the implications of AES implementation decisions for their ecological effectiveness. The main reason for AES adoption that was common across case study regions is the interplay of opportunity costs and payment levels, which has negative implications for the ecological effectiveness of AES as farmers prioritized marginal land or adopted non‐additional AES. Among reasons that vary across regions, tenure relations and the role of ecological reasoning stand out. We find that AES are unlikely to trigger broader shifts towards sustainable management but there is some potential for improvement, mainly by increasing the flexibility, spatial targeting and ecological ambition of the schemes. Read the free Plain Language Summary for this article on the Journal blog.